Gambaran Kasus Osteomielitis Kronis di Rumah Sakit Tingkat II Kartika Husada Kabupaten Kubu Raya Provinsi Kalimantan Barat Periode Januari 2015 – Desember 2017 - Cahayo Mahandro Mahandro; Ganda MRH Purba; Ery Hermawati (PT Kalbe Farma Tbk., 2024)
Osteomyelitis is a bacterial infection in bone or bone marrow. This study was a retrospective descriptive study of chronic osteomyelitis cases at Kartika Husada Level II Army Hospital of Kubu Raya Regency from January 2015 to December 2017 as well as a description of its management. There were 47 subjects taken based on their medical records. Surgical management was done in 39 cases (83.0%), consisting of debridement and sequestrectomy (33 cases), debridement (4 cases), and amputation (2 cases). Surgical management was combined with non-surgical management.